Prenatal care in Primary Health Care in Piauí from the perspective of users (Research, Society and Development, 2022)
Objective: To analyze and describe prenatal care in the state of Piauí from the perspective of users of Primary Care services. Methodology: The sociodemographic profile of women, quality of prenatal care, satisfaction with the UBS and with the assistance received by professionals were analyzed. Data were collected between November and December 2017. The population of this study consisted of 265 women who underwent postpartum consultations, interviewed at the time of the external evaluation in the third cycle of the PMAQ-AB, in the state of Piauí, in 990 health units where in these teams were allocated. Results: They indicated an average age of 27.6 years, income 3.4% lower than the minimum wage at the time, 78.6% married/stable union, 81.1% brown/mixed/black. 63.7% of them reported not having undergone the gynecological examination, but 98.0% had prenatal care, with an average of 7 consultations and 84.3% performed in the same basic health unit. 93.3% of the interviewees reported having received guidance on Exclusive Breastfeeding and 53.4% ​​of them were evaluated during the puerperium. The service provided by professionals had an assessment of 87.6% of very good and good. Conclusion: There is an effort from the teams in the care of pregnant women, that vulnerable pregnant women start prenatal care in a timely manner, carrying out what is recommended by the MS in relation to the number of prenatal consultations, but that there is a need for permanent education to improve and better prepare health professionals even more in puerperal care, and women already recognize the assistance received by the team of Primary Health Care professionals as positive